Primary school physical education management: Profiles and predictors in Central Java - Adi S; Hilmy Aliriad; Andi Nova; Guntur Firmansyah; Wahyu Arbanisa (UIR Press, 2023)
Effective management allows teachers to see and handle student learning problems. This study aimed to determine the physical education management of elementary school teachers in Central Java and its predictors. This research is quantitative with data description and correlation. Using purposive sampling, the total number of respondents was 50 physical education teachers at the elementary level in Central Java. The data was processed using descriptive statistics, data normality, and correlation. The subjects studied had a minimum teaching experience of 1 year. Data collection techniques include instruments and observation by physical education teachers. The instruments included planning, implementation, and evaluation of physical education management. The questionnaire uses a scale of 1-4. In terms of age and length of teaching, researchers used correlation analysis. Correlation data were processed using SPSS Version 21. The management of physical education in Central Java is in the